A preliminary study on the relationship of abiotic factors to the abundance of beach morning glory (ipomoea pes-caprae) between two beach locations / Nur Fitryanie Sapari and Patricia Natin - Sapari, Nur Fitryanie; Natin, Patricia (Universiti Teknologi MARA, Sabah, 2021)
The beach morning glory is utilized as traditional medicine by the public but studies about this plant are still lacking. This study aims to identify the effect of soil organic matter (SOM) and heavy metal concentration on the distribution and abundance of the beach morning glory between Lok Kawi Beach and Teluk Likas Beach in Sabah. Sampling was conducted in August 2020, prior to the implementation of Recovery Movement Control Order (RMCO). The field work experimental design for the sampling was based on line transect and quadrat sampling method. The plant abundance was determined by using the quadrat (point-intercept method). The soil organic matter was analysed by using the Loss on Ignition (LOI) method and the heavy metals concentration was analysed by using the Atomic Absorption Spectrophotometer (AAS). The results showed that the mean abundance of beach morning glory was higher in Teluk Likas Beach than in Lok Kawi Beach (p = 0.001). For the mean Lead (Pb) concentration, it was higher in Lok Kawi Beach than in Teluk Likas Beach (p = 0.01). The mean of soil organic matter (p = 0.88), zinc (Zn) (p = 0.12) and copper (Cu) (p = 0.54) did not differ much between both locations. For the correlation, the abundance of beach morning glory was not affected by the heavy metals' concentration (Pb, Zn and Cu). The relative abundance of beach morning glory was not affected by the SOM and heavy metals concentration. Further research is needed to determine its bioactive compounds and efficacy.